Keefektifan Lama Kontak Karbon Aktif Terhadap Penurunan Kadar Amonia Limbah Cair Industri Tahudi Desa Teguhan Sragen Wetan Sragen - Roesiani, Lina; , Haru Subaris Kasjono, SKM., M. Kes; , Dwi Astuti, SKM., M.Kes (2015)
Tofu Liquid Waste has smell that comes from the content of ammonia in it. The measurement result of tofu liquid waste in Teguhan of SragenWetan Village, Sragen districts has known that levels of ammonia is 30,6 mg/l so does not fulfill for a quality standard.The purpose of this research to determine contact timeofactived carbon that the most effective to reduce ammonia levels in tofu liquid waste with variations contact time of actived carbon 0 minutes (control), 3 minutes, 5 minutes, and 7 minutes. The methods of this research is an experimental study with a pretest-posttest design with control group. The population for this research are37 tofu industries and the techniques sampling using purposive sampling. The statistical test using One Way Anova with results of the analysis data obtained p value = 0.000 (<0.01), therefore it concluded that the contact time of actived carbon are the most effective to reduce levels of ammonia. In Post Hoc Test, known that contact 7 minutes had mean difference 4,16667, it means the contact 7 minutes has the highest a different value than contact 3 minutes and 5 minutes, this value indicates that the contact 7 minutes is the most effective time to reduce levels of ammonia to be 19,93 mg/l and fulfill for a quality standard.